Electronic Authentication as a Means of Protecting electronic signature - Messedek, Fatima-zohra (Journal of Legal Studies and Researches, 2020)
In this article we deal with electronic authentication as a means to protect the electronic signature, where we dealt with the electronic signature as a modern image of the signature, and then touched on the ratification or electronic authentication as a way to protect the electronic signature and authenticating electronic contracts. We have reached an important conclusion that the electronic certification ensures the authenticity of the electronic signature and thus cultivates trust among the customers through the network. Internet, which encourages electronic trade.